What role do nurses play and what are the cultural challenges they face in culture brokering in HIV/AIDS prevention activities in Mohale's Hoek District, Lesotho? - Lerotholi, Polo (My University, 2011)
This Research Report explores the cultural challenges faced by nurses in HIV/AIDS prevention activities in five Health Centers of Mohale’s Hoek, Lesotho. It investigates in turn what role nurses play as culture brokers. Lesotho faces major challenges from HIV/AIDS with high prevalence rates. Despite the governments’ significant efforts in the fight against the disease, these efforts have been largely unsuccessful in combating new infections. At the fore front of the struggle against HIV/AIDS nurses play a crucial role by providing services related to HIV prevention, treatment and care. With the increased burden of HIV/AIDS on nurses, expectation is that as biomedical Health Care providers nurses should go beyond the parameters of biomedicine and provide a more holistic approach towards provision of care and support to the patients and educating their patients about HIV/AIDS. In conclusion this research was able to suggest positive aspects of Sesotho culture that can be included in HIV/AIDS prevention interventions. This research focused on five Health Centers where fifteen face to face open-ended interviews with nurses at the Health Care Centers were carried out. The principle research method employed in this research was semi-structured interviews. The research findings show that nurses working in the five Health Centers are responsible for facilitating HIV/AIDS prevention activities. Their responsibilities in providing various HIV/AIDS services not only take place in Health Center settings but often take place in nearby villages through interactions with community members and administering the HIV/AIDS services while making their community visits. Nurses described some of the personal challenges they faced but a lot of the problems that nurses have to deal with which constrains their efforts in the prevention of HIV are mainly structural and cultural in nature, ranging from economic dependency, overexposure to HIV/AIDS prevention messages, youth culture and HIV/AIDS to current prevailing perceptions about HIV/AIDS, gender and socio-cultural practices and risky sexual behaviours that expose men and women to HIV. Overall the findings show first and foremost, though nurses are not aware of the concept of culture brokering, in fact they are not even aware that they are engaging in activities of brokering, the process of culture brokering is evidenced by the numerous activities that nurses engage with to successfully facilitate HIV/AIDS prevention strategies. Second, the awareness of nurses that there are differences in values, beliefs, and behaviors of the people and communities they service, and understanding that these values, beliefs and behaviors are the basis for the way people interact with each other form part of the process of brokering. Third, another important role within this process is what nurses decide to do with the information they have about the people they work with. By guiding them on how to protect themselves against HIV through educational talks, interactions in the communities, collaborations with other significant figures and translations of messages in Sesotho qualifies as a tactic in problem solving. Lastly, drawn from the nurses’ various opinions about what is suited as competent to be included in HIV/AIDS prevention strategies in Lesotho, the researcher was able to gather and conclude what aspects of Sesotho culture can be considered for inclusion in HIV/AIDS strategies.